Research on Vibration Numerical Analysis of Traction Motor of Metro Vehicle Based on Practical Line Conditions - Feng GUO; Yongsheng WANG; Yajie WANG (机车电传动)
Vibration data of the traction motor body during operation was obtained by the vibration test of the traction motor of a metro vehicle, and compared with relevant standards such as IEC 61373 . The analysis results showed that actual vibration magnitude of traction motor is lower than that specified in IEC 61373, but the impact magnitude is slightly higher than the standard value in the lateral direction, which provided guidance for the optimization of the motor design and reference for revision of IEC 61373.